Towards Robust Speech Models: Mitigating Backdoor Attacks via Audio Signal Enhancement and Fine-Pruning Techniques - Heyan Sun; Qi Zhong; Minfeng Qi; Uno Fang; Guoyi Shi; Sanshuai Cui (Mathematics)
The widespread adoption of deep neural networks (DNNs) in speech recognition has introduced significant security vulnerabilities, particularly from backdoor attacks. These attacks allow adversaries to manipulate system behavior through hidden triggers while maintaining normal operation on clean inputs. To address this challenge, we propose a novel defense framework that combines speech enhancement with neural architecture optimization. Our approach consists of three key steps. First, we use a ComplexMTASS-based enhancement network to isolate and remove backdoor triggers by leveraging their unique spectral characteristics. Second, we apply an adaptive fine-pruning algorithm to selectively deactivate malicious neurons while preserving the model’s linguistic capabilities. Finally, we fine-tune the pruned model using clean data to restore and enhance recognition accuracy. Experiments on the AISHELL dataset demonstrate the effectiveness of our method against advanced steganographic attacks, such as PBSM and VSVC. The results show a significant reduction in attack success rate to below 1.5%, while maintaining 99.4% accuracy on clean inputs. This represents a notable improvement over existing defenses, particularly under varying trigger intensities and poisoning rates.